Propagation of pariparoba (Piperaceae) by different types of stem cuttings and substrates - Aurea Portes Ferriani; Diones Krinski (Acta Biológica Catarinense, 2019)
Piper cernuum Vell., a native species known as pariparoba, presents essential oil with potential properties and significant growth in clearings, being indicated for the recovery of degraded areas. Prospecting studies for new botanical matrices need the development of specific essays of plant propagation for future domestication of the species. This work aimed to evaluate the rooting of different types of cuttings using different substrates to develop a seedling production protocol. Stem cuttings with one or two nodes were installed on three types of substrates (medium sifted sand, vermiculite of medium granulometry and commercial substrate [Tropstrato HP®]) and maintained in greenhouse for 60 days to evaluation of the percentages of survival, mortality, sprouts, rooting, average number and average length of the roots. The results showed interaction between cutting types and substrates for rooting percentage and sprouting cuttings. The largest rooting percentages were observed in apical cuttings planted in sand and vermiculite (57.0 and 55.25%, respectively). Cuttings with two nodes presented higher performance than those with one node when compared for the analyzed variables.